Reason and ethics: praxis and global governance (Research, Society and Development, 2021)
This article encourages the need to think about human action, a source of sustainable development – ​​global governance – reflecting on the various aspects of participatory and shared progress. In this sense, the question is: do government actions and policies promote citizenship, human dignity, development that is associated with the eradication of poverty? The objective is to explore reason and ethics as elements that make it possible to ensure the necessary praxis for global sustainability. As for the methodology, the research is exploratory and analytical with a qualitative approach, being carried out through a literature review. From this perspective, it is concluded that, understanding reason and ethics as the foundation of the values ​​on which human action takes place is of fundamental importance to ensure sustainable development. Furthermore, it is highlighted that public policies must be implemented in order to promote the education and training of the person so that they can act proactively. It is necessary to overcome predatory exploration and develop a new wisdom that encourages praxis in favor of a development that involves all human beings in the human family.